Nestin expression is dynamically regulated in cardiomyocytes during embryogenesis. Issue 4 (27th September 2017) - Hertig, Vanessa; Matos‐Nieves, Adrianna; Garg, Vidu; Villeneuve, Louis; Mamarbachi, Maya; Caland, Laurie; Calderone, Angelino
Abstract : The transcriptional factors implicated in the expression of the intermediate filament protein nestin in cardiomyocytes during embryogenesis remain undefined. In the heart of 9, 5–10, 5 day embryonic mice, nestin staining was detected in atrial and ventricular cardiomyocytes and a subpopulation co‐expressed Tbx5. At later stages of development, nestin immunoreactivity in cardiomyocytes gradually diminished and was absent in the heart of 17, 5 day embryonic mice. In the heart of wild type 11, 5 day embryonic mice, 54 ± 7% of the trabeculae expressed nestin and the percentage was significantly increased in the hearts of Tbx5 +/− and Gata4 +/− embryos. The cell cycle protein Ki67 and transcriptional coactivator Yap‐1 were still prevalent in the nucleus of nestin (+) ‐cardiomyocytes identified in the heart of Tbx5 +/− and Gata4 +/− embryonic mice. Phorbol 12, 13‐dibutyrate treatment of neonatal rat ventricular cardiomyocytes increased Yap‐1 phosphorylation and co‐administration of the p38 MAPK inhibitor SB203580 led to significant dephosphorylation. Antagonism of dephosphorylated Yap‐1 signalling with verteporfin inhibited phorbol 12, 13‐dibutyrate/SB203580‐mediated nestin expression and BrdU incorporation of neonatal cardiomyocytes. Nestin depletion with an AAV9 containing a shRNA directed against the intermediate filament protein significantly reduced the number of neonatal cardiomyocytes that re‐entered the cell cycle. These findings demonstrate that Tbx5‐ and Gata4‐dependent events negatively regulate nestin expression in cardiomyocytes during embryogenesis. By contrast, dephosphorylated Yap‐1 acting via upregulation of the intermediate filament protein nestin plays a seminal role in the cell cycle re‐entry of cardiomyocytes. Based on these data, an analogous role of Yap‐1 may be prevalent in the heart of Tbx5 +/− and Gata4 +/− mice. Abstract : In the heart of E10, 5 mice, nestin staining was detected in a partially striated pattern in cardiac troponin‐T‐immunoreactive cardiomyocytes. Nestin staining was also identified in endocardial cells lining embryonic cardiomyocytes.